Diseases in Florida Vegetable Garden Beans: Bush, Lima, Pole, Wax, Southern Peas, English Peas, and Snow Peas - Ken Pernezny; Aaron Palmateer; Tom Kucharek (EDIS)
The pathogenic microorganisms that attack garden vegetables, including Bush beans, Lima beans, Pole beans, Wax beans, Southern peas, English peas, and Chinese or Snow peas can be classified into four major groups: fungi, bacteria, nematodes, and viruses. This document is PP-209, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.